Предмет: Математика, автор: Аноним

Упростите выражение:
1) -1/9(3b-9)+1/3b
2) -19/8(4c+8/19)+19/2

Ответы

Автор ответа: nafanya2014
0
1)-frac{1}{9}cdot (3b-9)+frac{1}{3}b=-frac{1}{9}cdot 3b -frac{1}{9}cdot (-9)+frac{1}{3}b=-frac{1}{3}b+1+frac{1}{3}b=1 \ 2)-frac{19}{8}cdot (4c+ frac{8}{19} )+ frac{19}{2}=-frac{19}{8}cdot 4c-frac{19}{8}cdotfrac{8}{19} + frac{19}{2}= - frac{19}{2}c-1+ frac{19}{2}=
 - frac{19}{2}c- frac{2}{2} + frac{19}{2}=- frac{19}{2}c+ frac{17}{2}
Похожие вопросы
Предмет: Литература, автор: wkfjei
Предмет: Литература, автор: semasli2021